Efficiency Analysis Of Shrimp Cultivation In Kaur District (Case Study Of South Kaur District) - Ondi Fernando; Karona Cahya Susena; Herlin (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study is to determine the partial and simultaneous influence of the area of ​​ponds, seedlings, feed, medicines, and labor on the efficiency of shrimp farming in Kaur Regency.Type of quantitative descriptive research. Purposive sampling method using saturated sampling method and data analysis method used is multiple linear regression analysis method with SPSS.The results of this study are the value of R Square (Detremination) of 0.17. Variable area of ​​pond does not affect the efficiency of vannamei shrimp aquaculture in South Kaur Sub District shown with a significant value (0.763)> level of significance (α = 0.05). Seed variable did not affect the efficiency of vannamei shrimp farming in South Kaur Sub District indicated by a significant value (0.977)> of the level of significance (α = 0.05). Variable feed did not affect the efficiency of vannamei shrimp farming in South Kaur Sub District indicated by a significant value (0.958)> level of significance (α = 0.05). Drug variables did not affect the efficiency of vannamei shrimp farming in South Kaur Sub District is indicated by a significant value (0.651)> level of significance (α = 0.05). Labor variable does not affect the efficiency of vannamei shrimp farming in South Kaur Sub District significant value (0.778)> level of significance (α = 0, 05). Simultaneously or together variables of pool area, seedlings, feed, medicine, and labor have no influence on the efficiency of vannamei shrimp farming in South Kaur Sub District indicated by a significant value of 0.994> level of significance (α = 0.05 ).